ONLINE PROMOTION AND BRAND IMAGE ON CONSUMER DECISIONS - Yudhi Prasetya Mada; Roynaldi Novenda Putra (International Journal of Innovations in Engineering Research and Technology, 2023)
Study uses primary data, namely data obtained directly from consumers of Hj. Norm. The population of this research is consumers of Hj. Norma using a non-probability sampling technique, namely incidental sampling, with a sample of 100 respondents. The research instrument used a questionnaire and analyzed using multiple linear regression analysis with t test (partial) and f test (simultaneous). The results that online promotion has a significant effect on purchasing decisions and for brand image partially has a significant effect on purchasing decisions. Simultaneously, the two variables have a significant effect on purchasing decisions.